Design of Patient Complaint Information System at Qadr Hospital For Health Services Website Based - Ulum, Muhamad Bahrul; Syahiradania, Azahra (Poltanesa, 2023)
Hospitals are health care facilities that are required to create patient satisfaction. If the services they receive or enjoy are far below the standards they expect, then people will lose interest in getting these services or services. The mismatch between expectations and the services provided will lead to complaints and complaints from the public about the services provided, thus adversely affecting the image of the health care facility. The problem that occurs at Qadr Hospital is that it is difficult for patients to submit complaints about health services, although there is an assessment questionnaire in the form of a google form, the link cannot be accessed when the patient is at home so that user inconvenience can result in reduced patient participation in providing feedback, so that complaints that should be heard by the hospital can be missed, and hospital service quality has difficulty tracking and analysing patient complaints effectively so that it can hinder the process and service improvement. So that Qadr Hospital plans to create a website-based application that will be used as a medium to facilitate patients in channeling complaints related to the health services provided. In designing this application using the Rapid Application Development (RAD) development method.